2018
DOI: 10.1111/anu.12684
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary tryptophan levels on growth performance, whole body composition and gene expression levels related to glycometabolism for juvenile blunt snout bream,Megalobrama amblycephala

Abstract: To investigate the effects of dietary tryptophan on growth and glycometabolism in juvenile blunt snout bream, 450 fish (initial weight 23.33 ± 0.03 g) were fed six practical diets with graded levels of tryptophan (from 0.79 g/kg to 5.96 g/kg dry matter) for 8 weeks. Results showed that final weight, per cent weight gain (PWG), protein efficiency rate, feed intake and feed conversion ratio (FCR) were significantly improved by 2.80 g/kg diet. The maximum values of protein and ash were observed in 2.80 g/kg diet,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
1
6
1
Order By: Relevance
“…Further, the protein expression of SGLT1 in the jejunum and GLUT2 in the liver was decreased in the LBW-T0.4 group. Unlike our study, where we showed an increased mRNA abundance of GCK in LBW-T0.8, others have either failed to detect a change in the hepatic GCK mRNA expression in rats fed with diets supplemented with Trp [ 22 ] or showed a downregulation in the GCK expression in the liver with a higher dose of dietary Trp in blunt snout bream [ 69 ]. Differences in the amount of supplemented Trp and animal species used may contribute to the discrepancy in the findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, the protein expression of SGLT1 in the jejunum and GLUT2 in the liver was decreased in the LBW-T0.4 group. Unlike our study, where we showed an increased mRNA abundance of GCK in LBW-T0.8, others have either failed to detect a change in the hepatic GCK mRNA expression in rats fed with diets supplemented with Trp [ 22 ] or showed a downregulation in the GCK expression in the liver with a higher dose of dietary Trp in blunt snout bream [ 69 ]. Differences in the amount of supplemented Trp and animal species used may contribute to the discrepancy in the findings.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the mRNA levels of the gluconeogenesisrelated gene PEPCK were upregulated with high dietary lysine levels (4.09% dietary lysine level); its expression was higher in this group than in all other groups. Moreover, a high plasma GLU content was observed in the high lysine supplementation group, and this finding is similar to the findings of previous studies on the essential amino acids arginine [47] and tryptophan [48] in blunt snout bream (Megalobrama amblycephala). Our previous study indicated that gluconeogenesis could be stimulated by high lysine levels in grass carp [15].…”
Section: Akt/foxo1supporting
confidence: 91%
“…It has been introduced in many countries worldwide such as in Africa, North America and Eurasia (Habte‐Tsion et al, ). Accordingly, recent studies have been carried out to grasp the specific nutrient requirements on dietary carbohydrate (Zhou, Liu, Ge, Xie, & Xu, ), protein (Habte‐Tsion et al, ) and amino acids such as methionine (Liang et al, ), threonine (Habte‐Tsion, Ge, et al, ; Habte‐Tsion, Liu, et al, ), arginine (Ren et al, ) and tryptophan (Ji et al, ). However, few studies dealt with the issue of fish meal substitution by plant proteins in the diet of the target species such as rice protein concentrate, canola meal and cottonseed meal (Cai et al, ; Zhou, Habte‐Tsion, Ge, Liu, et al, ; Zhou, Habte‐Tsion, Ge, Xie, et al, ).…”
Section: Introductionmentioning
confidence: 99%